Association between electrocardiographic parameters and collateral circulation in patients with chronic total occlusion (Annals of Medical Research, 2021)
Aim: In patients with chronic total occlusion (CTO), negative cardiovascular outcomes (angina, more frequent ventricular arrhythmias, higher mortality) and reduced survival have been demonstrated. The association between several electrocardiogram (ECG) markers, revealing individuals at high risk for ventricular arrhythmia, and collateral has been investigated in different studies in coronary artery disease patients. In this study, we aimed to investigate the association between the electrocardiographic parameters between good coronary collateral group and poor coronary collateral group in CTO patients with PCI.Material and Methods: Patients retrospectively implemented CTO PCI to those with symptomatic symptoms of myocardial ischemia or with the exact sign of ischemia in the CTO area. The patients were divided into 2 groups according to the Rentrop class: group 1 (Rentrop 0 and 1) and group 2 (Rentrop 2 and 3). Baseline characteristics, laboratory and ECGs, procedural data, and outcome data were retrospectively collected. Results: In this study included 59 CTO patients undergoing PCI. Mean age was 61.0±10.3 years and 43 (72.9%) of patients were male, and PCI success was 69.4%. While 22 (37.2%) of the patients were poor collateral group 1 (Rentrop 0 and 1), the remaining 37 (62.3%) of them were good collateral group 2 (Rentrop 2 and 3). There was a significant difference, in poor and good collateral groups, QT dispersion (77.2±27.9 vs 66.5±22.5, p: 0.041, respectively), QTc dispersion (82.1±26.9 vs 70.4±23.9, p: 0.034, respectively), and the presence of fQRS (63.6% vs 43.2, p: 0.027, respectively). But there was no statistically difference in P wave dispersion (48.0±9.5 vs 47.2±11.3, p: 0.796). Correlation analysis reported the association between Rentrop classification and Syntax score (r: -0.397, p: 0.002), LDL-C (r: -0.198, p: 0.025), QT dispersion (r: -0.156, p: 0.045), QTc dispersion (r: -0.176, p: 0.037), and the presence of fQRS (r: 0.234, p: 0.021) were statistically significant.Conclusion: We suggest that some ECG parameters are an important, easy, simple, and cost effective tool and can be beneficial in predicting the poor or good collateral in patients with CTO.
Keywords: Chronic total occlusion; fragmented QRS; P wave dispersion; Rentrop collateral; ventricular repolarization; QTc dispersion